2019
DOI: 10.1111/ecog.04534
|View full text |Cite
|
Sign up to set email alerts
|

Do genetic structure and landscape heterogeneity impact color morph frequency in a polymorphic salamander?

Abstract: Landscape heterogeneity plays an important role in population structure and divergence, particularly for species with limited vagility. Here, we used a landscape genetic approach to identify how landscape and environmental variables affect genetic structure and color morph frequency in a polymorphic salamander. The eastern red‐backed salamander, Plethodon cinereus, is widely distributed in northeastern North America and contains two common color morphs, striped and unstriped, that are divergent in ecology, beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…Using microsatellite markers, they find a complex interaction between gene flow, genetic drift, and natural selection working together to explain morph frequencies, similar to Kraemer et al (2016). Using ecological niche modeling, Hantak et al (2019) found waterways were the most important factor in explaining morph frequency variation, likely, as the authors suggest, because they are strong dispersal barriers.…”
Section: (B) Systematics and Geographic Variationmentioning
confidence: 94%
See 4 more Smart Citations
“…Using microsatellite markers, they find a complex interaction between gene flow, genetic drift, and natural selection working together to explain morph frequencies, similar to Kraemer et al (2016). Using ecological niche modeling, Hantak et al (2019) found waterways were the most important factor in explaining morph frequency variation, likely, as the authors suggest, because they are strong dispersal barriers.…”
Section: (B) Systematics and Geographic Variationmentioning
confidence: 94%
“…At the time Petranka (1998) wrote his chapter on P. cinereus, there was evidence that striped morphs were more common in cooler climates (i.e., higher latitudes; Test, 1952;Lotter & Scott, 1977) and evidence that unstriped morphs had a physiology consistent with being more tolerant of warmer conditions than striped morphs (Moreno, 1989). However, more recent studies have identified exceptions to these general patterns and contradictory results that suggest high levels of local variation in both color phenotype frequency (e.g., Hantak et al, 2019) and color phenotype physiologies (e.g., Petruzzi, Niewiarowski, & Moore, 2006). For example, Petruzzi et al (2006) found that the patterns of physiological differences between color phenotypes first detected by (Moreno, 1989) in New Jersey were inconsistent and variable across several populations in Ohio.…”
Section: (B) Systematics and Geographic Variationmentioning
confidence: 99%
See 3 more Smart Citations